PENGARUH BAHAN AJAR MIKROBIOLOGI BERBASIS INKUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA IKIP BUDI UTOMO MALANG - Purwaning Budi Lestari; Triasih Wahyu Hartati (Program Studi Pendidikan Biologi, Fakultas Pendidikan Ilmu Eksakta dan Keolahragaan, IKIP Budi Utomo Malang, 2019)
The lack of availability of inquiry-based teaching materials causes student thinking to be less systematic. The purpose of this study was to determine the effect of inquiry-based microbiology teaching materials on students' critical thinking skills at IKIP Budi Utomo. This type of research is quasi-experiment with testing validity using the bivariate correlation method according to Pearson, while reliability testing uses the Cronbach Alpha method. The pretest values were tested using the t-test for free samples, while the difference between pretest and posttest in the trial class was analyzed using the General Linear Model (GLM) - Repeated Measures. Posttest value difference, the value of critical thinking skills, using the General Linear Model (GLM) - Multivariate. The results of the study showed that there was a significant influence between the development of inquiry-based instructional materials on students' thinking skills. This is shown to be significant at 0,000. In addition, there are meaningful differences in critical thinking skills, there are also mean differences of 19,000 for the control class and 23.4285 in the treatment class. Based on the results of the study, it can be concluded that there is an influence of inquiry-based microbiology teaching materials on the critical thinking ability of Budi Utomo IKIP students.